Learning to solve problems with technology : a constructivist perspective - Jonassen, David H.; Howland, Jane; Moore, Joi; Marra, Rose M (Upper Saddle River, N.J. : Merrill, 2003)
Rather than focus on technology as a tool to teach with, this text stresses that technology video, hypermedia, the Internet, etc.is an excellent tool to learn with. The emphasis is on learning to solve problems. By concentrating on problem solving with several specific media, the authors show how a variety of technologies can be used to engage students in personally and socially constructed meaning. They address the Internet, and how it can be used to foster community building; video, and how naturally students take to being behind the camera; and multimedia, as a new form of interactive literacy.--Source not specified.
Includes bibliographical references and index.
Keywords: Educational technology; Teaching -- Aids and devices; Learning; Constructivism (Education)